Educational potential of extracurricular foreign language activity in the system of higher education - Khvedchenya, Ludmila V. (Journal of the Belarusian State University. Journalism, 2019)
The article reveals the educational potential of extracurriculum foreign language activity in the system of higher education. It is asserted that foreign language activity integrates various forms of education: ideological, civil, patriotic, moral, multi-cultural, aesthetic, ecological, labour, professional, etc. Examples are provided to demonstrate the mechanisms for their successful implementation. Common preconditions for success are considered to be: the cultural content of the materials used, which makes it possible to present the whole integrated system of cultural values as a single object of education; the variety of forms of educational work, which entails the expansion of the educational environment to extracurriculum activity; the use of modern technologies (social and information) being an optional means of achieving educational targets. As a new trend professionally oriented type of education is described. An experience of the BSU English language department for humanities serves as an empirical base of the research.
Keywords: foreign language education; educational potential; expansion of the educational environment; extracurricular activity; Week of English; forms of educational activities; modern information technologies; professional education